STRATEGI PUBLIC RELATION DALAM MEMPERTAHANKAN CITRA POSITIF HOTEL SWIS-BELL HARBOUR BAY DIKOTA BATAM PASCA PANDEMI COVID-19 : PENDAHULUAN, KAJIAN TEORI, METODOLOGI PENELITIAN, HASIL DAN PEMBAHASAN, SIMPULAN, DAFTAR PUSTAKA - Sofian, Febby; Abidin, Sholihul (LPPM Universitas Putera Batam, 2024)
Swiss-Bell Harbour Bay Batam Hotel, impacted by the COVID-19 pandemic, undergoes a study aiming to unveil its post-pandemic image maintenance strategy. With qualitative methods, the research explores inhibiting and supporting factors influencing the hotel's public relations efforts. Using Cutlip, Center, and Broom's public relations strategies, the study employs interviews, documentation, observation, and literature studies for data collection. Public Relations adopts various tactics, emphasizing technological utilization, regular market analysis, events, CSR initiatives, and a consistent commitment to superior service quality. However, challenges persist, notably in employee turnover and reduced foreign guest visits post-COVID-19. Conversely, supporting factors include fostering a pleasant work environment, leveraging word-of-mouth marketing, and forming collaborations with other hotels. In essence, Swiss-Bell Harbour Bay Batam Hotel's post-pandemic image maintenance strategy hinges on technology, market awareness, and quality service, with challenges arising from employee turnover and diminished international guests countered by a positive workplace environment, effective marketing, and strategic partnerships.